An overview of percutaneous coronary intervention in dialysis patients: Insights from a Japanese nationwide registry. Issue 1 (23rd November 2018) - Numasawa, Yohei; Inohara, Taku; Ishii, Hideki; Yamaji, Kyohei; Hirano, Keita; Kohsaka, Shun; Sawano, Mitsuaki; Kuno, Toshiki; Kodaira, Masaki; Uemura, Shiro; Kadota, Kazushige; Amano, Tetsuya; et al.
Abstract: Objectives: This study sought to provide an overview of percutaneous coronary intervention (PCI) in dialysis patients from a Japanese nationwide registry. Background: Little is known about dialysis patients undergoing PCI because few are enrolled in clinical trials. Methods: We analyzed 624, 900 PCI cases including 41, 384 dialysis patients (6.6%) from 1, 017 Japanese hospitals between 2014 and 2016. We investigated differences in characteristics and in‐hospital outcomes between dialysis and nondialysis patients, and assessed factors associated with an increased risk of adverse outcomes. Results: Dialysis patients had more comorbidities than nondialysis patients and higher rates of complications including in‐hospital mortality (3.3% vs. 1.5%, respectively, in the acute coronary syndrome [ACS] cohort, 0.2% vs. 0.1% in the non‐ACS cohort) and bleeding complications requiring blood transfusion (1.1% vs. 0.4% in ACS, 0.5% vs. 0.2% in non‐ACS). Dialysis was significantly associated with an increased risk of in‐hospital mortality (odds ratio [OR]: 1.42, 95% confidence interval [CI]: 1.24–1.62 in ACS, OR: 2.25, 95% CI: 1.66–3.05 in non‐ACS) and bleeding (OR: 1.60, 95% CI: 1.30–1.96 in ACS, OR: 1.55, 95% CI: 1.27–1.88 in non‐ACS). For dialysis patients, age, acute heart failure, and cardiogenic shock were associated with an increased risk of in‐hospital mortality in the ACS cohort, whereas age, female gender, and history of heart failure were associated with higher in‐hospital mortality in the non‐ACS cohort. Conclusions: PCI was widely performed for dialysis patients with either ACS or non‐ACS in Japan. Dialysis patients had a greater risk of adverse outcomes than nondialysis patients after PCI.